Twórcy podstaw wojskowości i policji w Łodzi 1918-1919 - Kozłowski, Włodzimierz (Acta Universitatis Lodziensis. Folia Historica, 2001)
The restitution of the Polish state after the 123 years of national slavery urgently demanded the creation of military forces and police. Łódź was a seat of the VIII Military District (commander - Col. Albin Marian Jasiński from former Russian army), which comprised three administrative districts (powiaty): łódzki, brzeziński and łaski. The Łódź General District came into being on November 17th 1918. It was the basic element of the military division of the territory of the stale. General Jan Romer (from former Austro-Hungarian army) had been appointed the first commander of the District but unfortunately being the British prisoner of war he did not managed to returned to Poland on time. Therefore it was general Aleksander Osiński (from former Russian army) who in fact became the first commander of the Łódź General District in those circumstances. Colonel A. M. Jasiński was an organiser of the Łódź territorial infantry regiment which constituted the base for the future 28th Infantry Regiment of Children of Łódź. General A. Osiński who stay in Łódź till August 1919, organised the territorial structure of the command on the District's level, supervised the creation and developing of the structure of the recruiting boards for men and horses, controlled the formation of the military units and their dispatching to the front as well as the reinforcements for them. In the same time general Stanisław Suryn (from former Russian army) contributed very much to the process of the creation of Municipal Militia in Łódź and to disarmament of German troops in the town in November 1918. All three officers (A. M. Jasiński, S. Suryn i A. Osiński) rendered great services to the foundation of the cornerstone of the Polish statehood first in Łódź, and then with their activity as the commanders in the ranks of the army of the Second Republic of Poland.